Injury mechanisms and situational patterns of severe lower limb muscle injuries in male professional football (soccer) players: a systematic video analysis study on 103 cases - Villa, F. D.; Massa, B.; Bortolami, A.; Nanni, G.; Olmo, J.; Buckthorpe, M. (British Journal of Sports Medicine, 2023)
Objective The objective of this study is to describe the mechanism of injury and situational patterns (based on ball possession and playing action leading to injury) of severe (lay-off time >28 days) lower limb muscle injuries in professional male football (soccer) players during match play.